The Correlation Between Work Motivation and Work Discipline on Teacher Performance - Syafe'i Syafe'i; Alhadi Yan Putra; Nur Ahyani (research, training and philanthropy institution Natural Aceh, 2021)
This study aims to determine the correlation between work motivation and work discipline on teacher performance. The formulation of the problems in this study: (1) is there a correlation between work motivation and teacher performance?, (2) is there a correlation between work discipline and teacher performance?, (3) is there a correlation between work motivation and work discipline on teacher performance. This type of research is descriptive quantitative. The sample in this study amounted to 74 students. Data collection techniques in the form of tests and documentation. The instrument used was a test sheet. The theories used are teaching and learning strategy theory and learning evaluation theory. The results of this study. Based on the respondents' perceptions of work motivation, a score range of 116-150 was obtained, with a total score of 20409 and an average score of 130.79 which in this case was categorized as quite good. Respondents' perceptions about the effect of work discipline on teacher performance obtained a score range of 107 - 151, with a total score of 20191.00 and an average score of 134.43 which is in the good category. The degree of influence of the work motivation variable (X1) and the work discipline variable (X2) on teacher performance (Y) was 0.73 or 73%. This shows that the teacher's performance (Y) is jointly (simultaneously) influenced by the work motivation variable (X1) and the work discipline variable (X2) by 73% while the remaining 27% is influenced by other factors outside the equation model.